Cystatin C and albuminuria as predictors of long‐term allograft outcomes in kidney transplant recipients. (3rd February 2013) - Rodrigo, Emilio; Ruiz, Juan C.; Fernández‐Fresnedo, Gema; Fernández, Maria D.; Piñera, Celestino; Palomar, Rosa; Monfá, Elena; Gómez‐Alamillo, Carlos; Arias, Manuel
Abstract Although cystatin C (Cys) and albuminuria (Alb) are predictors of end‐stage renal disease in the general population, there are limited data about the performance of these markers alone or combined with respect to the prediction of the kidney transplant outcome. We assessed the ability of one‐yr creatinine (Cr), MDRD equation, Cys, Hoek equation, Alb, the logarithm of albuminuria (LogAlb), and two products of these variables for predicting death‐censored graft loss (DCGL) in 127 kidney transplant recipients. Mean follow‐up time was 5.6 ± 1.7 yr. During this time, 18 patients developed DCGL. The area under the receiver operating characteristic curve for DCGL ranged from 71.1% to 85.4%, with Cys*LogAlb being the best predictor. Cys‐based variables and variables combining LogAlb and renal function estimates have better discrimination ability than Cr‐based variables alone. After multivariate analysis, quartiles of all one‐yr variables (except of Cr and MDRD) were independent predictors for DCGL. Predictors combining Alb and a Cr‐ or Cys‐based estimate of renal function performed better than those markers alone to predict DCGL. Cys‐based predictors performed better than Cr‐based predictors. Using a double‐marker in kidney transplantation, it is possible to identify the highest risk group in which to prioritize specialty care.